2011
DOI: 10.1161/atvbaha.111.234062
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Liver, Abdominal Visceral Fat, and Cardiometabolic Risk Factors

Abstract: Objective To examine whether fatty liver, and abdominal visceral adipose tissue (VAT) are jointly associated with cardiometabolic abnormalities. Methods and Results African American participants were from the Jackson Heart Study (n=2882, 65% women) who underwent computed tomography. Fatty liver was measured by liver attenuation in Hounsfield Units (LA) and VAT was quantified volumetrically. Cross-sectional associations between LA, VAT, and cardiometabolic risk factors were assessed using linear and logistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
96
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(113 citation statements)
references
References 29 publications
8
96
0
9
Order By: Relevance
“…Categorization into four subgroups based on the ALT and visceral AT values revealed that women with an elevated ALT level, but not increased amount of visceral AT, had a higher odds ratio for IGT, indicating that the impact of ALT on post-challenge plasma glucose may be even stronger than that of visceral AT. The ALT and visceral AT values were found to be interrelated, in agreement with the findings of prior studies 6,7,14,19) . The correlation coefficients observed in the current study (r = 0.41 in men and r = 0.36 in women) are comparable to those reported in the Framingham Heart Study (0.31 in men and 0.21 in women) 14) and the Jackson Heart Study (−0.30) 19) , although in the latter study, the liver fat content was HDL-cholesterol in both genders (p<0.05 in men and p<0.001 in women) and hypertriglyceridemia in men (p<0.05).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Categorization into four subgroups based on the ALT and visceral AT values revealed that women with an elevated ALT level, but not increased amount of visceral AT, had a higher odds ratio for IGT, indicating that the impact of ALT on post-challenge plasma glucose may be even stronger than that of visceral AT. The ALT and visceral AT values were found to be interrelated, in agreement with the findings of prior studies 6,7,14,19) . The correlation coefficients observed in the current study (r = 0.41 in men and r = 0.36 in women) are comparable to those reported in the Framingham Heart Study (0.31 in men and 0.21 in women) 14) and the Jackson Heart Study (−0.30) 19) , although in the latter study, the liver fat content was HDL-cholesterol in both genders (p<0.05 in men and p<0.001 in women) and hypertriglyceridemia in men (p<0.05).…”
Section: Discussionsupporting
confidence: 91%
“…The ALT and visceral AT values were found to be interrelated, in agreement with the findings of prior studies 6,7,14,19) . The correlation coefficients observed in the current study (r = 0.41 in men and r = 0.36 in women) are comparable to those reported in the Framingham Heart Study (0.31 in men and 0.21 in women) 14) and the Jackson Heart Study (−0.30) 19) , although in the latter study, the liver fat content was HDL-cholesterol in both genders (p<0.05 in men and p<0.001 in women) and hypertriglyceridemia in men (p<0.05). The high-ALT/low-visceral AT group, but not the low-ALT/high-visceral AT group, had a significantly higher odds ratio for IGT in women (p< 0.05).…”
Section: Discussionsupporting
confidence: 91%
“…Studies on the contributions of VAT, SAT, and IHL to insulin resistance in the basal state have been ambiguous. Some argue in favor of mutually independent contributions of VAT and IHL (11,14), whereas others find that IHL, not VAT, associates with insulin resistance (5,15). Similarly, the SAT contribution to insulin resistance, independent of VAT, is both supported (2) and disputed (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…With the availability of magnetic resonance spectroscopy, very strong associations have been reported between liver fat content and features of the cardiometabolic risk profile predicting risk of type 2 diabetes mellitus and CVD. 106,107 Although Liu et al 48 have reported stronger correlations between cardiometabolic risk factors and visceral adipose tissue than with liver fat, some other studies have even suggested that the associations between visceral adiposity and diabetogenic and atherogenic metabolic complications could be entirely explained by the concomitant increase in liver fat content. 106,108 These results can be explained by the fact that the liver is a key organ that is central to the control of carbohydrate and lipid metabolism.…”
Section: Liver Fat In Visceral Obesity: a Key Ectopic Fat Depotmentioning
confidence: 99%